Cytotoxicity Evaluation of Bacteria Extract Isolated from Indonesia Sheep Manures and Fungal Fruiting Body - Hartiadi, Leonny Yulita; Winiati, Immaculata Titis; -, samirah -; Gomez, Cristina (Indonesia International Institute for Life Sciences, 2020)
Introduction: Cancer is one of the leading cause of death worldwide. Chemotherapy remains the most widely used approach to treat cancer. However, due to the lack of specificity, drug resistance, and undesirable side effects, the discovery of novel anticancer drugs is still a priority in cancer research. Bacteria are one of the major contributors for anticancer compounds as bacteria are able to produce secondary metabolites which may have cytotoxic activity. Method: A literature study was conducted to identify the isolates in i3L-USAID bacteria database that were potential candidates for novel anticancer drugs. The selected bacteria were cultured and their secondary metabolites were extracted. Cytotoxic activity of the extracts was assessed through morphological observation and MTT assay on HeLa and 3T3 fibroblast cell lines. Results: Aneurinibacillus sp. and Ochrobactrum sp. were selected. Ochrobactrum sp. extract significantly suppressed the growth of HeLa cells at 1000 µg/ml (p < 0.05) while it did not have any effect on 3T3 cells. Despite able to suppress the HeLa cell proliferation, Aneurinibacillus sp. extract significantly enhanced the growth of 3T3 fibroblast at the 1000 µg/ml (p < 0.05). The cytotoxicity activity was corroborated by cell death observed on HeLa cells treated with high concentrations of the extracts Conclusion: Secondary metabolites from Aneurinibacillus sp. and Ochrobactrum sp. could only exert cytotoxic effect at high concentration which is unfavourable for anticancer compounds. Although the extracts resulted in a reduction of HeLa cells proliferation, the extracts did not inhibit proliferation of 3T3, suggesting selectivity for non-tumorigenic over tumorigenic cells.